2016
DOI: 10.1002/gj.2759
|View full text |Cite
|
Sign up to set email alerts
|

A lower Viséan (Carboniferous) brachiopod fauna from the eastern Alborz Mountains, northern Iran, and its palaeobiogeographical implications

Abstract: The brachiopods from the upper part of the Mobarak Formation at the Kiyasar section in the eastern Alborz Mountains, northern Iran, have been studied in detail. Fifteen species assigned to 13 genera of Strophomenida, Orthotetida, Orthida, Productida, Athyridida and Spiriferida are described. The fauna is determined as early Viséan in age based on the presence of Eomarginifera paucispinosa, Grandispirifer mylkensis and Unispirifer sp., and their associated foraminifers Uralodiscus, Paraarchaediscus, Glomodiscus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The Mobarak Formation was introduced by Assereto () in the Mobarakabad area, central Alborz, and comprises black fossiliferous limestone with subordinate black marl in the lower part. It has been widely studied and dated in central Alborz using brachiopods (Bahrammanesh, Angiolini, Antonelli, Aghababalou, & Gaetani, ; Gaetani, , , ; Qiao, Falahatgar, & Shen, ), conodonts (Ahmadzadeh Heravi, ; Habibi et al, ), and foraminifers (Bozorgnia, ; Devuyst & Kalvoda, ; Falahatgar, Vachard, & Sakha, ; Vachard, ; Zandkarimi, ; Zandkarimi, Najafian, Vachard, Bahrammanesh, & Vaziri, ; Zandkarimi, Vachard, Cózar, et al, ; Zandkarimi, Vachard, Najafian, Hamdi, & Mosaddegh, ). The Mississippian of the north‐eastern Alborz in addition to the Mobarak Formation contains relatively similar strata to the Dozdehban Formation, which was referred to as the “Bagherabad Formation” (Leven & Gorgij, ; Lys, Stampfli, & Jenny, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Mobarak Formation was introduced by Assereto () in the Mobarakabad area, central Alborz, and comprises black fossiliferous limestone with subordinate black marl in the lower part. It has been widely studied and dated in central Alborz using brachiopods (Bahrammanesh, Angiolini, Antonelli, Aghababalou, & Gaetani, ; Gaetani, , , ; Qiao, Falahatgar, & Shen, ), conodonts (Ahmadzadeh Heravi, ; Habibi et al, ), and foraminifers (Bozorgnia, ; Devuyst & Kalvoda, ; Falahatgar, Vachard, & Sakha, ; Vachard, ; Zandkarimi, ; Zandkarimi, Najafian, Vachard, Bahrammanesh, & Vaziri, ; Zandkarimi, Vachard, Cózar, et al, ; Zandkarimi, Vachard, Najafian, Hamdi, & Mosaddegh, ). The Mississippian of the north‐eastern Alborz in addition to the Mobarak Formation contains relatively similar strata to the Dozdehban Formation, which was referred to as the “Bagherabad Formation” (Leven & Gorgij, ; Lys, Stampfli, & Jenny, ).…”
Section: Introductionmentioning
confidence: 99%
“…The brachiopods from the Alborz Mountains in northern Iran (Qiao et al 2017) have a strong affinity with the fauna of Azerbaijan, and were not far from Iran. Therefore, it will not be set up as a fossil location alone.…”
Section: Tethys Realmmentioning
confidence: 99%
“…Iran is considered to be a Gondwanan-derived block that broke off from the eastern margin of the Gondwana supercontinent in the late Paleozoic, moved northward across the Paleotethys, and eventually collided with the southern margin of Eurasia in the Late Triassic, creating the Eo-Cimmerian orogeny (Sengör, 1979; Besse et al, 1998; Ruban et al, 2007; Muttoni et al, 2009a, b; Zanchi et al, 2009, 2015; Berra and Angiolini, 2014). Paleomagnetic data obtained in northern Iran and Alborz (Besse et al, 1998; Muttoni et al, 2009a; Berra and Angiolini, 2014) suggest a location in the mid-latitude belt of the southern hemisphere, on the northern margin of Gondwana and the southern margin of the Paleotethys (Angiolini et al, 2007, 2013; Brenckle et al, 2009; Qiao et al, 2017; Vachard and Arefifard, 2015).…”
Section: Paleobiogeographic Implicationsmentioning
confidence: 99%
“…The presence of early Carboniferous warm-water smaller foraminifers (Zandkarimi et al, 2014; Vachard and Arefifard, 2015) and brachiopods (Brenckle et al, 2009; Bahrammanesh et al, 2011; Qiao et al, 2017) in Iran has been explained by counterclockwise oceanic currents and warm surface current gyres that brought warm taxa from the tropics toward intermediate latitudes (Kiessling et al, 1999; Angiolini et al, 2007; Brenckle et al, 2009). Other workers suggested that the Paleotethys was narrow during the early Carboniferous, facilitating faunal exchanges between its northern and southern margins, as well as the occurrence of warm water fauna along its southern margin (Zandkarimi et al, 2014; Falahatgar et al, 2015; Vachard and Arefifard, 2015).…”
Section: Paleobiogeographic Implicationsmentioning
confidence: 99%